Leaching and mass balance of 15N-labeled urea applied to a Kentucky bluegrass turf - Rieke, P. E., author; Paul, Eldor A., author; Branham, B. E., author; Miltner, E. D., author; Crop Science Society of America, publisher (Colorado State University. Libraries, 1996)
The fate of urea applied to Kentucky bluegrass (Poa pratensis L.) turf was studied over a 2-yr period using a combination of intact monolith lysimeters and small plots. Soil type was a Marlette fine sandy loam (fine-loamy, mixed mesic Glossoboric Hapludalfs). Urea was applied at a rate of 196 kg N ha−1 yr−1 in five equal applications of 39.2 kg N ha−1, using two application schedules. Treatments were fertilized at approximately 38-d intervals with the "Spring" treatment fertilized from late April through late September and the "Fall" treatment from early June through early November. In 1991 only, the April and November applications used 15N-labeled urea (LFN). For the Spring treatment, 31% of LFN was recovered from thatch at 18 DAT. This value remained constant for the next year, then gradually declined to 20% after 2 yr. Only 8% of the LFN was recovered from soil at 18 DAT and increased to only 20% 2 year after application. Approximately 35% of the LFN was harvested in clippings over 2 yr. Through May 1993 (748 DAT), LFN in leachate totaled 0.18% of the amount applied. For the Fall treatment, 62% of the LFN was recovered from thatch at 18 DAT. This value declined to 35% by the following June. LFN in soil increased from 12% to25% over 2 yr. Approximately 38% of the LFN was harvested in clippings over 2 yr. Total leachate LFN recovery was 0.23% over the 2-yr period. Total recovery of LFN was 64 and 81% for the Spring and Fall treatments, respectively, suggesting volatile losses of N. Whether the N was applied in the spring or late fall, rapid uptake and immobilization of the LFN resulted. A maximum of 25% of applied LFN was recovered in the soil from either application timing at any time over the 2 year of the experiment. A well-maintained turf intercepts and immobilizes LFN quickly making leaching an unlikely avenue of N loss from a turf system.
Keywords: cool season turf; chlorophyll; thatch; N fertilization